KEANEKARAGAMAN JENIS VEGETASI DI CAGAR ALAM LHO FAT PUN PIE KECAMATAN MONTERADO KABUPATEN BENGKAYANG - Putra, M Alihi; Burhanuddin, .; Manurung, Togar Fernando (JURNAL HUTAN LESTARI, 2019)
A nature reserve is a nature reserve area which because of its natural condition has a unique or unique type of plant or plant diversity along with natural phenomena and its ecosystem that requires protection and preservation so that its existence and development can take place naturally. The research objective was to obtain a variety of vegestation types, this study as a source of information regarding the diversity of vegetation in the Lho Fat Pun Fie Nature Reserve Monterado District, Bengkayang District. This research was conducted in Lho Fat Pun Fie Nature Reserve, Monterado District, Bengkayang Regency, this study was conducted 4 weeks in the field. The method used is a combination of lines and grid lines. Laying of the first line is purposive sampling, for the next paths are systematically sampling. The number of lanes used is 4 lanes with a length of 200 meters, each lane has 10 observation plots with an area of 1.6 ha. Based on an analysis of the diversity index of vegetation types in the Lo Fat Pun Fie Nature Reserve Monterado District, Bengkayang Regency is included in the medium category (H’1≤ H’≤3). Overall there are 35 types of vegetation ranging from the height of the seedlings to the level of the tree with a total of 1000 individuals. The species that dominate the study site are the tribe myrtaceae such as Syzygium liniatum, Syzygium grande, Rhodomytus tomentosa.Keyword : Lho Pat Pun Pie nature preserve, Monterado district, Vegetation diversity